A Hybrid Phototransistor Neuromorphic Synapse - Yu Liu; Wen Huang; Xiawa Wang; Renrong Liang; Jing Wang; Bin Yu; Tian-Ling Ren; Jun Xu (IEEE Journal of the Electron Devices Society, 2019)
In this paper, a synaptic transistor based on the indium zinc oxide (IZO)-hafnium oxide (HfO2) thin film structure was demonstrated. Blue light pulses (470 nm) were used as the presynaptic stimulus, the IZO channel was used as the postsynaptic membrane, and the HfO2 electrolyte film was regarded as the synaptic cleft. The synaptic transistor exhibited the behavior of paired-pulse facilitation. With different light power densities, the channel current of the transistor can be regulated to different levels, corresponding to different synaptic weights. In addition, the transistor showed the brain's memory behaviors including the short-term memory and the transition from the short to the long term memory. The synaptic behaviors of the transistor can be explained by the trapping and releasing processes of the photo-generated carriers.